A comparative study on fungal laccases immobilized on chitosan - Araújo,José Hilton Bernardino de (2005)
The phenoloxidase enzyme laccase from the cultures of the Pleurotus ostreatus and Botryosphaeria sp. and a commercial laccase from Aspergillus sp. were immobilized on chitosan of pharmaceutical degree by adsorption followed by crosslinking. Different immobilization conditions in relation to the granulometry of support and amount of enzymatic laccase extract used were tested, aiming at reaching high enzymatic activity with the immobilized enzyme. Two different substrates, ABTS and DMP, were used for the determination of enzymatic activity. The highest enzymatic activity was obtained when 1.0mg/mL of the enzymatic laccase extract from Botryosphaeria sp. was used with 1.0g of support (200 mesh). These immobilized enzymes are to be applied to the improvement of white wines by the degradation of undesirable phenolic compounds.